Economic imbalances and institutional changes to the Euro and the European Union - Mirdala, Rajmund; Canale, Rosaria Rita (International finance review ;, 2017)
This book offers a criticalperspective from which to observe evolution of the Euro Area and the European Union in these times of growing economic and political conflict. Key implications of design failures in the Euro Area (i.e. incorrect diagnostics ofthe public finance crisis, single monetary policy failure, heterogeneous macroeconomic environment, asymmetry in macroeconomic policies, obstacles forpolicy coordination) and their contribution to the excessive external andinternal economic imbalances will be critically discussed from the economic, policy and institutional perspectives. This critical insight is used to examineboth institutional asset and economic performance of Europe after the crisis, moving from the authors' shared perspective that the crisis revealed the weakaspects of the whole architecture of the European Union. The economic crisis revealed theexistence of different forms of imbalances inside the Eurozone and highlighted the flaws of the institutional architecture of economic policy in Europe. The greater fragility of some countries in respect to others has triggered abackward process in which national interests have started to prevail over those of both the currency area and the entire European Union. In turn, this has fuelled a progressive decline in confidence in the European institutions and iscreating growing questions of interpretation both in terms of economic theoryand institutional asset. This book focuses on these issues and on the degree of legitimacy of the European institutions resulting therefrom. It aims to investigate the nature and validity of the European integration process emphasizing limits and challenges arising from it.